Scalable risk assessment method for cloud computing using game theory (CCRAM) - Furuncu, Evrim; Soğukpınar, İbrahim (Elsevier, 2015)
Cloud computing is one of the most popular information processing concepts of today's IT world. The security of the cloud computing is complicated because each service model uses different infrastructure elements. Current security risk assessment models generally cannot be applied to cloud computing systems that change their states very rapidly. In this work, a scalable security risk assessment model has been proposed for cloud computing as a solution of this problem using game theory. Using this method, we can evaluate whether the risk in the system should be fixed by cloud provider or tenant of the system. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Cloud computing security; Scalable security using cloud service models; Game theory security modeling